ANALISI YURIDIS PEMUTUSAN HUBUNGAN KERJA (PHK) AKIBAT KESALAHAN BERAT (Studi kasus Putusan No No 1112 K/Pdt-Sus-PHI/2017 dan Putusan No 140 K/Pdt-Sus-PHI/2017) - Dodi Ikhsan Utama (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2022)
This study aims to analyze the implementation of Termination of Employment Due to Gross Errors after the application of Constitutional Court Decision No.012/PUU-I/2003 in Supreme Court Decision No. 112 K/Pdt-Sus-PHI/2017 and Decision No. 140 K/Pdt-Sus-PHI/2017. The research method used is a normative juridical research method, which is a study of a norm of legislation and legislation both historically, systematically, comparatively, synchronization, and on general legal principles. According to Constitutional Court Decision Number 012/PUU-I/2003 related to Termination of Employment due to gross errors is a decision that is not implemented due to the existence of Supreme Court Circular Letter Number 03 of 2015 concerning the Implementation of the Formulation of the Results of the Plenary Meeting of the Supreme Court Chamber in 2015 as a Guideline for the Implementation of Duties for the Court, dated December 29, 2015, letter B, item 2 of the Special Civil Code (e) that In the event of a layoff of a employees/worker for reasons of gross errors ex Article 158 of Law Number 13 of 2003 concerning Manpower (after the Constitutional Court Decision Number 012/PUU-I/2003, dated October 28, 2004), then the layoff can be carried out without having to wait for a criminal verdict of permanent legal force.